Status of COVID-19 vaccination around South Asia - Mahnoor Hayat; Mohammad Uzair; Rafay Ali Syed; Muhammad Arshad; Shahid Bashir (Taylor & Francis Group, 2022)
The public health sector and the global economy are facing the challenges of the epidemic of coronavirus disease 19 (COVID-19) since December 2019. Severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) is an emerging outbreak and spreading rapidly across the globe. The COVID-19 pandemic of unprecedented proportions has devastated almost all countries and pervaded globally. However, various vaccines have been developed to achieve immunity against the virus and limit transmissibility. By 18 November 2021, 52.6% of the world population got first dose of the COVID-19 vaccine. South Asia shares 15% fully vaccinated and 22.6% partially vaccinated population in the world. The 56.5% of South Asian Association Regional Cooperation (SAARC) regions, consisting of Pakistan, Afghanistan, Bangladesh, India, Sri Lanka, Nepal, Maldives, and Bhutan, got the first shot of COVID-19 vaccine, whereas 30.5% were fully vaccinated. India has the highest percentage of the vaccinated population of about 46.5% among SAARC countries. Although South Asian countries have unstable multiple socio-economic factors, including poverty, overpopulation, low literacy about medical care and medical systems, etc., the increasing trend in vaccination status has been observed. The high percentage of health budgets of SAARC countries was utilized for purchasing COVID-19 vaccines. This report observes that South Asian countries have been significantly tackling the threats of COVID-19.